A high-strength corrosion-resistant chrome-plated bolt and preparation method thereof
By forming the LaNi5 alloy powder intermediate layer on the bolt surface, combined with stabilizer, pulse plating and hydrogen removal technology, the problem of insufficient quality of the trivalent chromium plating layer is solved, and chrome-plated bolts with high strength and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411816292.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Traditional hexavalent chromium chromium plating technology poses a potential threat to the environment and human health, and the coating quality of trivalent chromium plating is not sufficient to meet the high strength and corrosion resistance requirements of aviation bolts.
Plasma spraying technology is used to form the intermediate layer of LaNi5 alloy powder on the surface of the bolt, and stabilizers are added to the electroplating chromium liquid to improve the stability of the trivalent chromium liquid. The chromium plating layer is formed by combining pulse plating and DC plating technology, and finally hydrogen removal is carried out to Improve the quality of the coating.
It significantly improves the strength and corrosion resistance of chrome-plated bolts, enhances the bonding force between the plating layer and the bolt substrate, and meets the requirements of higher strength and corrosion resistance of aviation bolts.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal surface treatment, and more specifically, to a high-strength, corrosion-resistant, chrome-plated bolt and a preparation method thereof. Background Art
[0002] Chrome-plated bolts are fasteners that are plated with a layer of chrome on the surface of the bolts through an electroplating process to enhance their corrosion resistance and aesthetics. Chrome-plated bolts can maintain good corrosion resistance in harsh environments and are not easy to rust and corrode. The surface of the chrome-plated bolts is smooth and bright, with a rich metallic texture. In addition, due to their good wear resistance and corrosion resistance, chrome-plated bolts have a relatively long service life.
[0003] During flight, aircraft will try their best to avoid various harsh environments such as high temperature, high humidity, salt spray, etc. Chrome-plated bolts can effectively resist the erosion of these environmental factors with their excellent corrosion resistance, thereby extending the service life of the bolts and ensuring the safe operation of the aircraft. In the aviation field, bolts need to withstand huge tensile and shear forces. The chrome plating layer of chrome-plated bolts has high hardness and wear resistance, which can significantly improve the mechanical properties of the bolts and ensure the structural integrity and stability of the aircraft.
[0004] With the continuous development of aviation technology, the application areas of chrome-plated bolts are also constantly expanding. In addition to traditional aircraft structure connections, chrome-plated bolts are also widely used in the assembly of aircraft engines, the connection of avionics systems and other fields.
[0005] However, the traditional bolt chrome plating process uses hexavalent chromium for chrome plating. The use of hexavalent chromium poses a potential threat to the environment and human health. Therefore, it is necessary to develop a more environmentally friendly, high-strength, and corrosion-resistant chrome plating technology. In recent years, environmentally friendly chrome plating technology that uses trivalent chromium to replace hexavalent chromium has gradually emerged. However, the quality of the chrome plating layer obtained by using trivalent chromium as the chrome plating liquid currently needs to be improved. Aviation chrome-plated bolts have higher requirements for their strength and corrosion resistance. It is necessary to provide new solutions for bolts with higher requirements for coating quality to meet their requirements. Summary of the invention
[0006] In order to use trivalent chromium as a chrome plating solution to chrome-plate bolts to obtain a coating with higher strength and corrosion resistance to meet its high requirements, the present application provides a high-strength and corrosion-resistant chrome-plated bolt and a preparation method thereof.
[0007] In a first aspect, the present application provides a method for preparing a high-strength, corrosion-resistant, chrome-plated bolt, using the following technical solution:
[0008] A method for preparing a high-strength corrosion-resistant chrome-plated bolt comprises the following steps:
[0009] S1. Pretreatment: clean the bolts, degrease them and then rinse them with water;
[0010] S2, intermediate layer treatment: using plasma spraying technology to coat the mixed powder of LaNi5 alloy powder and nickel powder on the pre-treated bolt surface to form an intermediate layer;
[0011] S3, chrome plating: placing the bolts after the intermediate layer treatment in step S2 in a chrome plating solution to which a trivalent chromium source and a stabilizer are added for electroplating;
[0012] S4, post-treatment, washing, drying and dehydrogenation treatment are performed on the bolts after electroplating in step S3 in sequence to obtain chrome-plated bolts.
[0013] By adopting the above technical scheme, the quality of the chrome-plated layer formed by electroplating with trivalent chromium plating solution is poor. On the one hand, this is because the stability of trivalent chromium is poor and it is easy to be converted into hexavalent chromium, which affects the stability of the electroplating solution and the quality of the coating; on the other hand, due to the presence of electroplating and electroplating chromium plating solution, hydrogen will be generated due to the occurrence of electrochemical reactions during the electroplating process. The hydrogen will be absorbed by the bolts. The hydrogen atoms absorbed by the bolts will diffuse inside the metal and gather at defects such as inclusions or cracks. The gathered hydrogen atoms will re-react to hydrogen molecules and form high pressure at the defects. With continuous diffusion and aggregation, hydrogen embrittlement will eventually occur, and hydrogen embrittlement will lead to reduced bonding strength and affect corrosion resistance and strength.
[0014] Therefore, in the present application, on the one hand, a stabilizer is added to the electrochromium plating solution to improve the stability of the trivalent chromium solution. On the other hand, in the present application, after the bolts are cleaned and degreased, a LaNi5 (AB5 type) alloy powder is firstly sprayed on the surface by plasma to form an intermediate layer. The LaNi5 alloy powder has Ni as the main metal element and La as a rare earth element. In the formation of the intermediate layer, the rare earth metal can react with hydrogen to generate rare earth hydride, thereby realizing the initial hydrogen storage, thereby reducing the absorption of hydrogen by the bolt matrix during the chromium plating process, and reducing the probability of hydrogen penetrating into the bolt interior to cause hydrogen embrittlement. In the later stage, dehydrogenation treatment is carried out to remove the stored hydrogen in the alloy powder, fundamentally reducing the poor quality of the coating caused by hydrogen embrittlement and improving the quality of the coating. The LaNi5 alloy intermediate layer has good corrosion resistance. The formation of the intermediate layer can further improve the corrosion resistance of the overall coating. The use of plasma spraying can also increase the bonding strength between the bolt and the chrome plating layer to prevent the coating from peeling off. Finally, the chrome plating layer obtained by the method provided in the present application has high strength, better corrosion resistance and better coating bonding, meeting the higher requirements of high strength and corrosion resistance.
[0015] Optionally, the added mass ratio of LaNi5 alloy powder to nickel powder is 1:(1.2-1.5).
[0016] By adopting the above technical scheme, the current aviation bolt material is mainly titanium alloy or high-strength steel, especially high-strength steel is more widely used. Since the chemical properties of nickel are relatively stable, it has better corrosion resistance and high temperature resistance, and its surface activity is lower than that of carbon steel, which is conducive to the adsorption and reduction of trivalent chromium on its surface, so that the trivalent chromium electroplating and nickel base are better bonded; therefore, when the intermediate layer in the present application uses LaNi5 alloy powder and nickel powder, LaNi5 alloy powder as a rare earth hydrogen storage alloy powder helps to solve the hydrogen embrittlement phenomenon, and the addition of nickel powder helps to improve the problem of weak bonding strength between the current trivalent chromium electroplating technology and the substrate, and also helps to reduce the occurrence of hydrogen embrittlement. In the present application, an intermediate layer is first formed between the chrome-plated layers, which significantly improves the corrosion resistance and strength performance of the chrome-plated bolts.
[0017] Optionally, the nickel powder is selected from spherical nickel powder and thorny spherical nickel powder with a particle size of 20-30 nm in a mass ratio of 1: (0.6-0.8).
[0018] By adopting the above technical solution, the surface of the spherical nickel powder is covered with nano-sized thorny structures, which helps to enhance the adhesion to the base layer and the chrome plating layer and enhance the bonding strength. The surface of the spherical nickel powder is smooth and easy to disperse, which is conducive to forming a uniform coating during the electroplating process. In addition, the spherical nickel powder can provide good wettability, which helps the chrome plating layer to spread and combine on the intermediate layer. This application uses the above two forms of nickel powder, and ultimately obtains chrome-plated bolts with better overall performance.
[0019] Optionally, in step S2, during the plasma spraying process, the spraying distance is 50-100 mm, the spraying power is 15-25 kw, the spraying speed is 120-150 mm / s, and the spraying thickness is 250-300 nm.
[0020] By adopting the above technical solution and controlling the above parameters, the bonding strength between the intermediate layer and the bolt and the chrome plating layer and the comprehensive performance of the formed comprehensive plating layer are better.
[0021] Optionally, the chromium electroplating solution in step S3 includes the following raw materials:
[0022] 30-70g / L trivalent chromium salt, 0.1-0.2g / L stabilizer, 30-50g / L complexing agent, 120-150g / L conductive salt, 50-80g / L buffer.
[0023] By adopting the above technical scheme, the trivalent chromium salt in the present application provides trivalent chromium ions, the conductive eye increases the conductivity of the plating solution, the addition of the buffer can be used to maintain the pH value of the plating solution to meet the electroplating requirements, the addition of the complexing agent can form a complex with the trivalent chromium salt, and convert the inert trivalent chromium into an easily deposited complex with high electrical activity, thereby improving the quality of the coating, and the stabilizer can prevent the trivalent chromium from being oxidized to hexavalent chromium, and at the same time reduce the hexavalent chromium present in the plating solution to trivalent chromium, thereby improving the stability of the plating solution and improving the quality of the coating.
[0024] Optionally, the trivalent chromium salt is chromium sulfate, the conductive salt is one or more of sodium sulfate, potassium sulfate and ammonium sulfate; the buffer is one or more of boric acid, aluminum sulfate and citric acid; the complexing agent is one or both of glycolic acid and citric acid;
[0025] The stabilizer includes at least one or more of sodium sulfite, neutral amino acid, methanol, sodium hypophosphite and ferrous sulfate.
[0026] Optionally, the stabilizer is selected in a mass ratio of 1: (1.2-1.5): (0.1-0.2) sodium sulfite, neutral amino acid and PAMAM.
[0027] By adopting the above technical scheme, the stabilizer of the present application is mainly composed of sodium sulfite and neutral amino acid, and a small amount of PAMAM is added. Sodium sulfite can form a complex with trivalent chromium ions on the one hand, further stabilize the chromium ions in the plating solution, and prevent the chromium ions from being oxidized to hexavalent chromium. Moreover, sodium sulfite, as a strong reducing agent, effectively inhibits and reduces the production of hexavalent chromium in the plating solution; and neutral amino acids can not only form stable complexes with trivalent chromium ions, but also play a buffering role in the pH of the plating solution, and can also increase the wettability of the plating solution, making it easier to spread on the surface of the intermediate layer, and a small amount of PAMAM not only has good complexing ability and can form a stable complex with trivalent chromium, but more importantly, it has excellent dispersibility, can be used as an interface fusion agent, to form a more uniform and stable plating solution, which helps to improve the quality of the coating, and the addition of a small amount of PAMAM introduces a small amount of nitrogen into the chromium plating layer, which can form nitrides with the chromium element, further improving its corrosion resistance and coating adhesion, and improving the quality of the coating.
[0028] Optionally, the neutral amino acid is one or more of glycine, glutamic acid and alanine.
[0029] Optionally, the chromium electroplating solution is prepared by the following method:
[0030] Dissolve trivalent chromium salt in water, add buffer and mix and stir, then add complexing agent, stir at 50-70°C for 30-50 minutes, add conductive salt and stabilizer, stir for 2-4 hours, adjust the pH of the plating solution to 2.5-4.5, continue stirring for 2-3 hours, and then let stand to obtain the electroplating chromium solution.
[0031] Optionally, when preparing the chromium electroplating solution, 0.05-0.1 g / L of sodium methane disulfonate is added together with the conductive salt.
[0032] By adopting the above technical solution, sodium methane disulfonate is used as a chrome plating brightener, which can significantly increase the deposition rate of hard chrome electroplating and improve the current efficiency of the electroplating process by more than 25%. It also helps to form a bright chromium layer and improve hardness and corrosion resistance.
[0033] Optionally, during the chrome plating process, the plating temperature is 45-60°C.
[0034] Optionally, chrome plating is performed by direct current electroplating, and the current density during electroplating is 1-3A / dm².
[0035] By adopting the above technical solution and controlling the electroplating temperature and current density, the quality of the plating layer is improved.
[0036] Optionally, when chrome plating, first use pulse current electroplating for 20-30 minutes and then continue with DC electroplating. During pulse electroplating, the pulse frequency is 2500-3000Hz, the pulse duty cycle is 20-40%, and the current density is 5-10A / dm².
[0037] By adopting the above-mentioned technical scheme, in this application, pulse electroplating is first used to form a coating on the intermediate layer, and the rapid change of current in the pulse electroplating process is used to generate impact force, which helps to increase the bonding force between the coating and the intermediate layer. At the same time, pulse electroplating can reduce defects such as pores and cracks in the coating. Then, DC electroplating is performed, which makes the coating thickness more controllable, and pulse electroplating forms a denser and more uniform coating. It can also shorten the electroplating time and significantly improve the final coating quality. Finally, a combination of pulse electroplating and DC electroplating is adopted in this application, which not only significantly improves the bonding strength between the chrome plating layer and the intermediate layer, but also significantly improves its corrosion resistance and other coating qualities. Finally, the intermediate layer is formed by plasma spraying after acidification in this application, and then by pulse electroplating, the current bonding strength defect between the trivalent chromium coating and the bolt base layer is solved, and the service life of the coating is improved.
[0038] Optionally, the dehydrogenation treatment operation in step S4 is:
[0039] Keep the chrome-plated bolts at 130-150℃ for 60-90min.
[0040] By adopting the above technical solution, the chrome-plated bolts are subjected to the above temperature baking treatment to effectively release and remove the hydrogen element in the rare earth alloy in the middle layer, thereby improving the hardness, strength and corrosion resistance of the bolts.
[0041] In a second aspect, the present application provides a high-strength, corrosion-resistant, chrome-plated bolt, which adopts the following technical solution:
[0042] A high-strength corrosion-resistant chrome-plated bolt is prepared by a preparation method of a high-strength corrosion-resistant chrome-plated bolt.
[0043] By adopting the above technical solution, the chrome-plated bolts prepared by the method in the present application have more excellent strength and corrosion resistance, meeting the high requirements of aviation bolts.
[0044] In summary, this application has the following beneficial effects:
[0045] 1. In the present application, on the one hand, a stabilizer is added to the electroplating chromium solution to improve the stability of the trivalent chromium solution. On the other hand, in the present application, after the bolts are cleaned and degreased, a LaNi5 (AB5 type) alloy powder is firstly sprayed on the surface by plasma spraying to form an intermediate layer. The LaNi5 alloy powder has Ni as the main metal element and La as a rare earth element. In the formation of the intermediate layer, the rare earth metal can react with hydrogen to form a rare earth hydride, thereby realizing the initial hydrogen storage, thereby reducing the absorption of hydrogen by the bolt matrix during the chromium plating process, and reducing the probability of hydrogen penetration into the bolt to cause hydrogen embrittlement. In the later stage, a dehydrogenation treatment is performed to remove the stored hydrogen in the alloy powder, fundamentally reducing the poor quality of the coating caused by hydrogen embrittlement and improving the quality of the coating;
[0046] 2. When LaNi5 alloy powder and nickel powder are used as the intermediate layer in the present application, LaNi5 alloy powder as a rare earth hydrogen storage alloy powder helps to solve the hydrogen embrittlement phenomenon, and the addition of nickel powder helps to improve the problem of weak bonding strength between the current trivalent chromium electroplating technology and the substrate, and also helps to reduce the occurrence of hydrogen embrittlement. In the present application, an intermediate layer is first formed between the chrome-plated layers, which significantly improves the corrosion resistance and strength performance of the chrome-plated bolts; and the use of plasma spraying can also improve the bonding strength between the bolts and the chrome-plated layer, and prevent the coating from peeling off. Finally, the chrome-plated layer obtained by the method provided in the present application has high strength, better corrosion resistance and better coating bonding, which meets the higher requirements of high strength and corrosion resistance. DETAILED DESCRIPTION
[0047] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0048] The bolt substrate in the following embodiments is a 30CrMnSiA alloy steel bolt.
[0049] In the following examples, the LaNi5 alloy powder is lanthanum-nickel alloy powder LaNi5 produced by Baotou Lanthanide New Material Technology Co., Ltd., wherein the La content is 32.1% and the Ni content is 67.9%. Example 1
[0050] A method for preparing a high-strength corrosion-resistant chrome-plated bolt comprises the following steps:
[0051] S1. Pretreatment: The bolts are first preliminarily cleaned with deionized water to remove dust and impurities on the surface, then degreased with an alkaline detergent, and then pickled and activated in a 20% mass concentration dilute sulfuric acid solution for 15 minutes, then washed with water and dried;
[0052] S2, intermediate layer treatment: LaNi5 alloy powder and nickel powder are mixed in a mass ratio of 1:1.3 to obtain a mixed powder, and then the mixed powder of LaNi5 alloy powder and nickel powder is coated on the pretreated bolt surface by plasma spraying technology to form an intermediate layer. The specific parameters of plasma spraying are: spraying distance of 80mm, spraying power of 20kw, spraying speed of 130mm / s, and spraying thickness of 280nm. The nickel powder is selected from spherical nickel powder and thorny spherical nickel powder with a particle size of 20-30nm in a mass ratio of 1:0.7;
[0053] S3, chrome plating: prepare chrome electroplating solution: prepare materials according to 50g / L trivalent chromium salt, 0.15g / L stabilizer, 40g / L complexing agent, 130g / L conductive salt, 65g / L buffer and 0.08g / L sodium methyl disulfonate brightener;
[0054] Dissolve trivalent chromium salt in water, add a buffer and mix and stir, then add a complexing agent, stir at 60°C for 40 minutes, add a conductive salt, a stabilizer and a brightener, stir for 3 hours, adjust the pH of the plating solution to 3, continue stirring for 2.5 hours, and then stand to obtain a chromium electroplating solution;
[0055] Among them, the trivalent chromium salt is chromium sulfate, the conductive salt is sodium sulfate; the buffer is boric acid; the complexing agent is glycolic acid; the stabilizer is sodium sulfite, neutral amino acid and PAMAM in a mass ratio of 1:1.3:0.15, and the neutral amino acid is glutamic acid;
[0056] The bolts treated with the intermediate layer in step S2 are placed in the above-obtained chromium electroplating solution for electroplating at a temperature of 50° C., with a graphite rod as an anode, and direct current electroplating is performed at a current density of 2A / dm²;
[0057] S4, post-treatment, washing, drying and dehydrogenation treatment are performed on the bolts after electroplating in step S3 in sequence, and the dehydrogenation treatment operation is: keeping the chrome-plated bolts at 140° C. for 70 minutes, and then cooling them to obtain chrome-plated bolts. Example 2
[0058] A method for preparing a high-strength corrosion-resistant chrome-plated bolt comprises the following steps:
[0059] S1. Pretreatment: The bolts are first preliminarily cleaned with deionized water to remove dust and impurities on the surface, then degreased with an alkaline detergent, and then pickled and activated in a 20% mass concentration dilute sulfuric acid solution for 10 minutes, then washed with water and dried;
[0060] S2, intermediate layer treatment: LaNi5 alloy powder and nickel powder are mixed in a mass ratio of 1:1.2 to obtain a mixed powder, and then the mixed powder of LaNi5 alloy powder and nickel powder is coated on the pretreated bolt surface by plasma spraying technology to form an intermediate layer. The specific parameters of plasma spraying are: spraying distance of 50mm, spraying power of 15kw, spraying speed of 120mm / s, and spraying thickness of 250nm. The nickel powder is selected from spherical nickel powder and thorny spherical nickel powder with a particle size of 20nm in a mass ratio of 1:0.6;
[0061] S3, chrome plating: prepare chrome plating solution: prepare materials according to 30g / L trivalent chromium salt, 0.1g / L stabilizer, 30g / L complexing agent, 120g / L conductive salt, 50g / L buffer and 0.05g / L sodium methyl disulfonate brightener;
[0062] Dissolve trivalent chromium salt in water, add a buffer and mix and stir, then add a complexing agent, stir at 50°C for 50 minutes, add a conductive salt, a stabilizer and a brightener, stir for 2 hours, adjust the pH of the plating solution to 2.5, continue stirring for 2 hours, and then stand to obtain a chromium electroplating solution;
[0063] Among them, the trivalent chromium salt is chromium sulfate, the conductive salt is ammonium sulfate; the buffer is boric acid and aluminum sulfate in a mass ratio of 1:1; the complexing agent is glycolic acid; the stabilizer is sodium sulfite, neutral amino acid and PAMAM in a mass ratio of 1:1.2:0.1, and the neutral amino acid is glycine;
[0064] The bolts treated with the intermediate layer in step S2 are placed in the above-obtained chromium electroplating solution for electroplating at a temperature of 45° C., with a graphite rod as an anode, and direct current electroplating is performed at a current density of 3A / dm²;
[0065] S4, post-treatment, washing, drying and dehydrogenation treatment are performed on the bolts after electroplating in step S3 in sequence, and the dehydrogenation treatment operation is: keeping the chrome-plated bolts at 130° C. for 90 minutes, and then cooling them to obtain chrome-plated bolts. Example 3
[0066] A method for preparing a high-strength corrosion-resistant chrome-plated bolt comprises the following steps:
[0067] S1. Pretreatment: The bolts are first preliminarily cleaned with deionized water to remove dust and impurities on the surface, then degreased with an alkaline detergent, and then pickled and activated in a 20% mass concentration dilute sulfuric acid solution for 20 minutes, then washed with water and dried;
[0068] S2, intermediate layer treatment: LaNi5 alloy powder and nickel powder are mixed in a mass ratio of 1:1.5 to obtain a mixed powder, and then the mixed powder of LaNi5 alloy powder and nickel powder is coated on the pretreated bolt surface by plasma spraying technology to form an intermediate layer. The specific parameters of plasma spraying are: spraying distance of 100mm, spraying power of 25kw, spraying speed of 150mm / s, and spraying thickness of 300nm. The nickel powder is selected from spherical nickel powder and thorny spherical nickel powder with a particle size of 20-30nm in a mass ratio of 1:0.8;
[0069] S3, chrome plating: prepare chrome electroplating solution: prepare materials according to 70g / L trivalent chromium salt, 0.2g / L stabilizer, 50g / L complexing agent, 150g / L conductive salt, 80g / L buffer and 0.1g / L sodium methyl disulfonate brightener;
[0070] Dissolve trivalent chromium salt in water, add a buffer and mix and stir, then add a complexing agent, stir at 70°C for 30 minutes, add a conductive salt, a stabilizer and a brightener, stir for 4 hours, adjust the pH of the plating solution to 4.5, continue stirring for 3 hours, and then stand to obtain a chromium electroplating solution;
[0071] Among them, the trivalent chromium salt is chromium sulfate, the conductive salt is sodium sulfate; the buffer is boric acid; the complexing agent is glycolic acid; the stabilizer is sodium sulfite, neutral amino acid and PAMAM in a mass ratio of 1:1.5:0.2, and the neutral amino acid is alanine;
[0072] The bolts treated with the intermediate layer in step S2 are placed in the above-obtained chromium electroplating solution for electroplating at a temperature of 60° C., with a graphite rod as an anode, and direct current electroplating is performed at a current density of 1 A / dm²;
[0073] S4, post-treatment, washing, drying and dehydrogenation treatment are performed on the bolts after electroplating in step S3 in sequence, and the dehydrogenation treatment operation is: keeping the chrome-plated bolts at 150° C. for 60 minutes, and then cooling them to obtain chrome-plated bolts. Example 4
[0074] A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt is carried out according to the method in Example 1, except that sodium sulfite is used as a stabilizer. Example 5
[0075] A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt is carried out according to the method in Example 1, except that sodium sulfite and glutamic acid are selected as a stabilizer in a mass ratio of 1:1.3. Example 6
[0076] A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt is carried out according to the method in Example 1, except that all the nickel powder in step S2 is spherical nickel powder. Example 7
[0077] A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt is carried out according to the method in Example 1, except that, in step S3, chrome is first electroplated with a square wave pulse current for 25 minutes and then with a direct current electroplating, and during the pulse electroplating, the pulse frequency is 2800 Hz, the pulse duty cycle is 30%, and the current density is 8 A / dm². Example 8
[0078] A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt is carried out according to the method in Example 1, except that, during the chrome electroplating in step S3, square wave pulse current electroplating is first used for 20-30 minutes and then direct current electroplating is continued. During the pulse electroplating, the pulse frequency is 3000 Hz, the pulse duty cycle is 20%, and the current density is 5 A / dm². Example 9
[0079] A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt is carried out according to the method in Example 1, except that, during the chrome electroplating in step S3, square wave pulse current electroplating is first used for 20-30 minutes and then direct current electroplating is continued. During the pulse electroplating, the pulse frequency is 2500 Hz, the pulse duty cycle is 40%, and the current density is 10 A / dm². Example 10
[0080] A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt is carried out according to the method in Example 7, except that the pulse frequency of the pulse current is 2000 Hz.
[0081] Comparative Example 1
[0082] A method for preparing high-strength, corrosion-resistant, chrome-plated bolts is carried out according to the method in Example 1, except that step S2 is not performed, and the bolts pretreated in step S1 are directly subjected to the chrome plating operation in step S3.
[0083] Comparative Example 2
[0084] A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt is carried out according to the method in Example 1, except that in step S2, an equal amount of LaNi5 alloy powder is replaced by nickel powder to form a nickel-based intermediate layer.
[0085] Comparative Example 3
[0086] A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt is carried out according to the method in Example 1, except that in step S2, an equal amount of nickel powder is replaced by LaNi5 alloy powder to form an alloy intermediate layer.
[0087] Comparative Example 4
[0088] A method for preparing a high-strength, corrosion-resistant chrome-plated bolt is carried out according to the method in Example 1, except that no stabilizer is added to the chromium electroplating solution in step S3.
[0089] Performance Testing
[0090] The chrome-plated bolts in the embodiments and comparative examples of the present application are finally electroplated to a thickness of 6 μm by controlling the electroplating time, and then the chrome-plated bolts prepared in the embodiments and comparative examples of the present application are subjected to hardness and corrosion resistance tests, wherein the corrosion resistance test adopts a copper ion accelerated salt spray test (CASS test), the test temperature is 50°C, the salt spray solution is a sodium chloride solution with a mass concentration of 5%, and copper chloride with a sodium chloride addition amount of 10% is doped therein, and the time when corrosion spots, rust or bubbles appear on the sample is observed. In addition, the chrome-plated bolts prepared in the embodiments and comparative examples of the present application are subjected to a thermal shock test, specifically: heating to 300°C and then keeping warm for 2 hours, then water cooling to room temperature, continuing to heat and raise the temperature to 300°C and then water cooling, and after 20 cycles in sequence, the percentage of coating peeling area is counted, and the statistical results are shown in Table 1 below.
[0091] Table 1:
[0092]
[0093] Table 1 continued:
[0094]
[0095] Referring to the test results in Table 1 above, the hardness of the chrome-plated bolts obtained in Examples 1-3 of the present application is above 600, and the chrome-plated bolts obtained have better strength, and the corrosion resistance does not show corrosion spots, red rust and the like in the copper ion accelerated salt spray test for more than 78 hours, and it can be seen that the bonding force between the coating and the bolt matrix in the present application is better. Combined with the test results of Example 1, Example 4 and Example 5, it can be seen that when PAMAM is not added to the stabilizer, the final coating quality is reduced, and the stabilizer helps to maintain the stability of trivalent chromium, thereby forming a more uniform and dense coating, improving the coating quality and better bonding with the bolt substrate. Combined with the test results of Example 6, when all spherical nickel powders are used for the nickel powder in the intermediate layer, the bonding force between the coating and the substrate is significantly reduced, and the final corrosion resistance is also reduced. Combined with the test results of Examples 7-9, when the chromium plating is performed in step S3, the pulse plating is first performed and then the DC plating is performed, and the final coating bonding force is more excellent and its corrosion resistance is better. Combined with the test results of Example 10, when the pulse current frequency is low, it will affect the bonding force between the coating and the substrate, and its corrosion resistance will also be slightly reduced, affecting the quality of the coating.
[0096] Referring to the test results of Example 1 and Comparative Example 1, it can be seen that when the intermediate layer treatment in step S2 is not performed, the bonding force between the coating and the substrate is significantly reduced, and the corrosion resistance is also reduced. Referring to the test results of Comparative Examples 2 and 3, when the intermediate layer adopts a single nickel layer or alloy layer, the bonding performance between the coating and the substrate is reduced, and the quality of the coating is also reduced. Combined with the test results of Comparative Example 4, when no stabilizer is added to the chromium plating solution, the quality of the coating is reduced.
[0097] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a high-strength, corrosion-resistant, chrome-plated bolt, characterized in that: The following steps are involved: S1. Pretreatment: clean the bolts, degrease them and then wash them with water; S2, intermediate layer treatment: using plasma spraying technology to coat the mixed powder of LaNi5 alloy powder and nickel powder on the pre-treated bolt surface to form an intermediate layer; S3, chrome plating: placing the bolts treated with the intermediate layer in step S2 in a chrome plating solution to which a trivalent chromium source and a stabilizer are added for electroplating; S4, post-treatment, washing, drying and dehydrogenation treatment are performed on the bolts after electroplating in step S3 in sequence to obtain chrome-plated bolts.
2. The method for preparing a high-strength corrosion-resistant chrome-plated bolt according to claim 1, characterized in that: The added mass ratio of LaNi5 alloy powder to nickel powder is 1:(1.2-1.5).
3. The method for preparing a high-strength corrosion-resistant chrome-plated bolt according to claim 1, characterized in that: The nickel powder is selected from spherical nickel powder and thorny spherical nickel powder with a particle size of 20-30 nm in a mass ratio of 1: (0.6-0.8).
4. The method for preparing a high-strength corrosion-resistant chrome-plated bolt according to claim 1, characterized in that: In step S2, during the plasma spraying process, the spraying distance is 50-100 mm, the spraying power is 15-25 kW, the spraying speed is 120-150 mm / s, and the spraying thickness is 250-300 nm.
5. The method for preparing a high-strength corrosion-resistant chrome-plated bolt according to claim 1, characterized in that: The chromium electroplating solution in step S3 includes the following raw materials: 30-70 g / L trivalent chromium salt, 0.1-0.2 g / L stabilizer, 30-50 g / L complexing agent, 120-150 g / L conductive salt, 50-80 g / L buffer; the conductive salt is selected from one or more of sodium sulfate, potassium sulfate and ammonium sulfate.
6. The method for preparing a high-strength, corrosion-resistant, chrome-plated bolt according to claim 5, characterized in that: The trivalent chromium salt is chromium sulfate, the buffer is one or both of boric acid and aluminum sulfate; the complexing agent is one or both of glycolic acid and citric acid.
7. The method for preparing a high-strength corrosion-resistant chrome-plated bolt according to claim 5, characterized in that: The stabilizer is selected in a mass ratio of 1: (1.2-1.5): (0.1-0.2) sodium sulfite, neutral amino acid and PAMAM.
8. The method for preparing a high-strength, corrosion-resistant, chrome-plated bolt according to claim 5, characterized in that: The chromium electroplating solution is prepared by the following method: Dissolve trivalent chromium salt in water, add buffer and mix and stir, then add complexing agent, stir at 50-70°C for 30-50 minutes, add conductive salt and stabilizer, stir for 2-4 hours, adjust the pH of the plating solution to 2.5-4.5, continue stirring for 2-3 hours, and then let stand to obtain the electroplating chromium solution.
9. The method for preparing a high-strength corrosion-resistant chrome-plated bolt according to claim 1, characterized in that: The dehydrogenation treatment operation in step S4 is: keeping the chrome-plated bolts at a temperature of 130-150° C. for 60-90 minutes.
10. A high-strength, corrosion-resistant chrome-plated bolt, characterized in that: The high-strength, corrosion-resistant, chrome-plated bolt is prepared by the preparation method of the high-strength, corrosion-resistant, chrome-plated bolt as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Porous nickel composite electrode, electroplating solution and preparation method of porous nickel composite electrode
CN102899681A
Environment-friendly electroplating liquid and electroplating process
CN105018973A